Pengembangan Usaha Bisnis Kuliner Luwiih Cafe - Iffah Fitria Nursolichah; Idris Idris (Faculty of Economics and Business Diponegoro University, 2025)
One of the strategic sectors that plays an important role in supporting Indonesia's economic growth is the food and beverage industry. Population growth is one of the factors contributing to the increase in coffee consumption in Indonesia. In terms of population growth, Cirebon Regency has promising prospects for the future, one of which is as a consumer of coffee. The challenges faced by companies today include insufficient implementation of promotional and marketing strategies, resulting in the Luwiih Cafe brand remaining relatively unknown to the public as a place for socializing and working from coffee across all age segments. This study aims to understand the direction and objectives of Luwiih Cafe, assess the market potential of Luwiih Cafe in Cirebon Regency, and create a business map for Luwiih Cafe in Cirebon Regency. This study employs a qualitative method with a descriptive approach. Data collection was conducted through observation to obtain primary data. Documentation methods were used to obtain secondary data. Luwiih Cafe has significant potential to expand its consumer base Based on market analysis. The implementation of a facility availability approach with a personalized touch has been developed as a marketing strategy by Luwiih Cafe. Product quality presents a unique challenge for Luwiih Cafe's operations. Therefore, Luwiih Cafe consistently strives to enhance quality control in its production processes. The implementation of recruitment and selection is a crucial step for the sustainability of Luwiih Cafe. By placing individuals according to their expertise, potential issues can be minimized. Daily coordination meetings with employees are conducted via a WhatsApp Group, and monthly meetings are held in person. Business legality, in the form of a Business Identification Number (NIB), is required to protect business activities. In terms of economics, Luwiih Cafe employs workers from Cirebon Regency. Luwiih Cafe can expand its market reach, strengthen its brand image, and enhance customer satisfaction by collaborating with micro-influencers and food bloggers to conduct reviews and endorsements, thereby increasing Luwiih Cafe's visibility on social media and optimizing the use of digital platforms.